Simian Varicella Virus Pathogenesis - Mahalingam, Ravi (2010)
Because varicella zoster virus (VZV) is an exclusively human pathogen, the development of an animal model is necessary to study pathogenesis, latency, and reactivation. The pathological, virological, and immunological features of simian varicella virus (SVV) infection in nonhuman primates are similar to those of VZV infection in humans. Both natural infection of cynomolgus and African green monkeys as well as intrabronchial inoculation of rhesus macaques with SVV provide the most useful models to study viral and immunological aspects of latency and the host immune response. Experimental immunosuppression of monkeys latently infected with SVV results in zoster, thus providing a new model system to study how the loss of adaptive immunity modulates virus reactivation.